1995
DOI: 10.1007/978-3-7091-3078-0
|View full text |Cite
|
Sign up to set email alerts
|

The Human Brain Stem and Cerebellum

Abstract: This work is subject to copyright. All rights are reserved, whether the whole or part of the material is concerned, specifically those of translation, reprinting, re-use of illustrations, broadcasting, reproduction by photocopying machines or similar means, and storage in data banks © 1995 Springer-VerlaglWien Softcover reprint of the hardcover 1st edition 1995

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 82 publications
(186 reference statements)
0
44
0
2
Order By: Relevance
“…The location of the contralateral somatosensory thalamus was defined by overlaying the change in low-frequency power with functional activation during repeated innocuous brushing of the right side of the mouth as reported previously (Henderson et al, 2013). The location of all other clusters were derived from our previous investigations and human brain atlases (Duvernoy, 1995;Paxinos and Huang, 1995;Mai et al, 2007), and we are confident that the changes reported encompass the nuclei described. We confirmed that these infraslow oscillations were restricted to the frequency range of 0.03-0.06 Hz by extracting and plotting the entire frequency range (0 -0.25 Hz; Fig.…”
Section: Altered Infra-slow Oscillations In Ascending Pain Pathwaysmentioning
confidence: 70%
See 1 more Smart Citation
“…The location of the contralateral somatosensory thalamus was defined by overlaying the change in low-frequency power with functional activation during repeated innocuous brushing of the right side of the mouth as reported previously (Henderson et al, 2013). The location of all other clusters were derived from our previous investigations and human brain atlases (Duvernoy, 1995;Paxinos and Huang, 1995;Mai et al, 2007), and we are confident that the changes reported encompass the nuclei described. We confirmed that these infraslow oscillations were restricted to the frequency range of 0.03-0.06 Hz by extracting and plotting the entire frequency range (0 -0.25 Hz; Fig.…”
Section: Altered Infra-slow Oscillations In Ascending Pain Pathwaysmentioning
confidence: 70%
“…For each cluster, power spectra were calculated, and significant differences between acute pain and no pain subjects were determined in the same process described above (two-sample t test, p Ͻ 0.05). The anatomical locations of each significant cluster were confirmed using the Atlas of the Human Brainstem and Cerebellum (Duvernoy, 1995) and the Atlas of the Human Brain (Mai et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…For the ventral striatum and midbrain, radius 10 mm spheres were defined on the basis of a previous study examining responses to visual cues of impending taste rewards . Anatomical labeling of activations was checked with reference to the atlases of Duvernoy (1995Duvernoy ( , 1999 by overlaying activations onto the mean normalized structural T1 image across participants. For visualizing activations, group maps are overlaid on the ICBM 152 structural template, an average T1-weighted image of 152 individuals coregistered to Montreal Neurological Institute (MNI) space.…”
Section: Methodsmentioning
confidence: 99%
“…Abbreviations: R, Raphe nuclei (serotoninergic); ret, nuclei reticularis including adrenergic and noradrenergic centers; VII, facial nucleus; Amb, nucleus ambiguus; IX, glossopharyngeal nucleus; NTS, nucleus tractus solitarius; GC, gracile (medial) and cuneate (lateral) nuclei (in blue). Line drawing is adapted from Duvernoy (1995) showing approximate position of nuclei. R (right) and L (left) indicate image orientation.…”
Section: The Effect Of Remifentanil On Respiratory Interoceptionmentioning
confidence: 99%